Dietary Arginine Supplementation Improves Intestinal Mitochondrial Functions in Low-Birth-Weight Piglets but Not in Normal-Birth-Weight Piglets - Hao Zhang; Ping Zheng; Daiwen Chen; Bing Yu; Jun He; Xiangbing Mao; Jie Yu; Yuheng Luo; Junqiu Luo; Zhiqing Huang; Hui Yan (MDPI AG, 2021)
Our previous studies revealed that L-arginine supplementation had beneficial effects on intestinal barrier functions of low-birth-weight (LBW) piglets, which were associated with the enhanced antioxidant capacity. Moreover, mitochondrial functions are closely related to the redox state. This study was to explore potential mechanisms of L-arginine-induced beneficial effects against intestinal dysfunction by regulating mitochondrial function of LBW piglets. Twenty 4-day-old normal birth weight (NBW) piglets (BW: 2.08 ± 0.09 kg) and 20 LBW siblings (BW: 1.16 ± 0.07 kg) were artificially fed either a basal diet or a basal diet supplemented with 1.0% L-arginine for 21 d, respectively. Growth performance, intestinal morphology, redox status, mitochondrial morphology, and mitochondrial functions were examined. Data were subjected to two-way analysis of variance. LBW piglets presented lower (p < 0.05) ADG, shorter (p < 0.05) intestinal villus height, lower (p < 0.05) jejunal adenosine triphosphate (ATP) content and higher (p < 0.05) concentrations of Ca2+ and 8-OH-dG in jejunal mitochondria, compared with NBW piglets. Supplementation with 1.0% L-arginine significantly increased (p < 0.05) ADG, the activities of CAT, SOD, and GPx, intestinal villus height and mRNA abundances of ZO-1 (2-fold) in the jejunum of LBW piglets, but not in NBW piglets. Furthermore, the concentrations of ATP and the transcription of COX IV, COX V genes were up-regulated (p < 0.05) and the concentration of Ca2+ and 8-OH-dG were decreased (p < 0.05) in arginine-treated LBW piglets. The results suggest that mitochondrial morphology is affected, and mitochondrial functions are impaired in the jejunum of LBW piglets. While supplementation with 1.0% L-arginine relieved intestinal dysfunction through enhancing antioxidant capacity and improving mitochondrial functions via repairing mitochondrial morphology, normalizing mitochondrial calcium, and increasing ATP concentration in the jejunum of LBW piglets. However, supplementation with L-arginine has no significant beneficial effects on intestinal health in NBW piglets.